Рассказы - Чехов Антон Павлович (Пушкинская библиотека, 2000)
Экземпляры: ЧЗ (20160311) / Инвентарный номер: 35336 / Цена: 35.25 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Ч-56 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1